"Factors influencing sedentary time and physical activity early after stroke: a qualitative study". Issue 14 (3rd July 2022) - Simpson, Dawn B.; Jose, Kim; English, Coralie; Gall, Seana L.; Breslin, Monique; Callisaya, Michele L.
Abstract: Purpose: We aimed to understand from the perspective of stroke survivors and their carers (1) factors contributing to sedentary time and physical activity during inpatient rehabilitation and the transition home, and (2) actual and perceived opportunities to reduce sedentary time and increase physical activity. Material and methods: Qualitative study with 7 stroke survivor/carer dyads and 8 stroke survivors. Semi-structured interviews were conducted 2–4 weeks after hospital discharge, audio recorded and transcribed prior to thematic analysis. Results: Stroke survivors were mean age 69 [SD15] years (53% male). Carers were mean age 62 [SD15] years (86% were female). Five themes were identified: (1) Education and guidance about physical activity and sedentary behaviour after stroke is important to build understanding of recovery and secondary prevention, (2) Stroke survivors need clear communication about safety and risk, (3) Return to life participation supports motivation for and engagement in physical activity, 4) Social and professional influences and 5) Opportunities to be physically active. Conclusion: Stroke survivors and their carers need a clearer understanding of the role of physical activity and risks of sedentary time during stroke recovery. Physical activity enablers included consistent communication, building confidence and skills to self-manage activity before discharge. Implications for Rehabilitation: Inpatient rehabilitation and early after discharge may be an important time-point to support stroke survivors to establish long term physical activity behaviours before contact with healthcare professionals reduces. To reduce sedentary behaviour, people need to understand the health benefits of breaking up sedentary time and people who need physical support to stand up will need greater support from health professionals. Being able to imagine a future post-stroke self is important motivation to get up and move. Rehabilitation should help develop a person's vision of their post-stroke self. Managing potential risks in hospital without overly restricting physical activity is important and requires consistent communication from the multi-disciplinary team. Building a person's confidence and skills to self-manage physical activity in the community prior to discharge home may be another key enabler for activity.